(untitled) (Journal of the College of Languages (JCL), 2025)
Pedro Salinas’ poetry was distinguished among other poets who preceded him, as he tended in his poems to theatrical weaving in order to be close to the recipient in terms of influence and impact. Thus, Pedro Salinas is considered one of the important innovators in Spanish literature, and he gained his wide fame in this approach, which made him count among the generation of 1927 at a young age. He infiltrated the theatrical presentation through his poetic creations, which added a special flavor to his theatrical creations. He wrote fourteen theatrical works that were able to occupy a position that was emulated by many of his generation and those who followed him with a taste for the intellectual and humanitarian topics that he dealt with in his theatrical productions. What distinguished Salinas’s theatrical works was the way he used poetic language in the theatrical complex. We find that his theater was sometimes a special theater and the other was pure poetry. He was drawn to the theater in intellectual and organizational narratives, but he quickly returned to his poetic origins and made us sympathize with the balanced poetic systems. ¿Cómo podía Salinas crear una línea propia dentro las tendencias literarias modernistas? ¿Cómo podía ser muy cerca del pensamiento de su sociedad cuando vivía fuera de España? Para contestar estas preguntas deseamos exponer un planteamiento investigado en las páginas más importantes de la literatura castellana contemporánea. Los primeros años del siglo XX, se han distinguido con una ola de tendencias y la aumentación de las ideas creadas fuera y dentro de España, Las ideologías que lo rodean se han influido muchísimo en la producción literaria español. Debido a esto, nació en Pedro Salinas un sentido profundo, que la identificación de la literatura sea particular, se adhiere a su ser humano territorial y geográfico y a todos sus símbolos morales y materiales, lejos de toda intrusión o influencia. Este fue un asunto tangible en los objetivos de las proposiciones literarias a principios del siglo pasado. Muchos escritores se distinguieron por este sentido, que luego se intensificó, hasta el punto de que algunos de ellos se convirtieron en pioneros de movimientos intelectuales, como el Surrealismo, que pasó a estar muy relacionado con Salvador Dalí, y el Impresionismo, que dependía de García Lorca, y otros similares.